Psychotropic medication use in adults with intellectual disability in Queensland, Australia, from 1999 to 2015: a cohort study. Issue 1 (2nd September 2019) - Song, M.; Ware, R.; Doan, T. N.; Harley, D.
Abstract: Background: Longitudinal data on medication use in adults with intellectual disability (ID) are scarce. We describe the longitudinal use of and factors associated with psychotropic medication prescribing in adults with ID living in the Australian community. Methods: Longitudinal data were obtained from adults with ID in the community in Queensland, Australia, between 1999 and 2015. Participant characteristics and medication use information were extracted from baseline questionnaires and health check booklets. Logistic regression was used to investigate the associations between participant characteristics and psychotropic medication use, commencement or cessation. Results: Longitudinal data were available for 138 participants on 697 reviews. The proportion of participants prescribed psychotropic medications increased from 43% to 54% between 1999 and 2015. The rates of commencement and cessation of psychotropic medications between consecutive time periods ranged from 9% to 18% and 7% to 15%, respectively. Challenging behaviour was associated with psychotropic medication use (adjusted odds ratio = 4.1; 95% confidence interval: 2.1–7.9). Presence of challenging behaviour, either consistent or newly identified, was positively associated with ongoing use or commencement of psychotropic medications. Conclusions: Psychotropic medications are commonly prescribed to adults with ID. Challenging behaviour is positively associated with ongoing use and commencement.